2014
DOI: 10.1002/ange.201406632
|View full text |Cite
|
Sign up to set email alerts
|

Bright, Highly Water‐Soluble Triazacyclononane Europium Complexes To Detect Ligand Binding with Time‐Resolved FRET Microscopy

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Recent years have seen efforts to engineer lanthanide complexes for cell-based, TGL biosensing and imaging applications including sensing of pH, metal ions, nucleic acids, enzymatic activities, and PPIs (Aulsebrook et al, 2018;Mathieu et al, 2018;New et al, 2010;Rajendran et al, 2014;Zhang et al, 2018). A number of studies reported proof-of-concept LRET microscopic imaging of molecular interactions between Tb(III)or Eu(III)-labeled and fluorophore-labeled species on cell surfaces including G-protein-coupled receptor (GPCR) ligand binding (Delbianco et al, 2014), GPCR oligomerization (Comps-Agrar et al, 2012;Faklaris et al, 2015), cadherin interactions (Linden et al, 2015), and interactions between complementary morpholino probes in zebrafish embryos (Cho et al, 2018). LRET between Tb(III) complexes and quantum dots on cell surfaces and in zebrafish has been shown to be an effective approach to signal amplification and multiplexing (Afsari et al, 2016;Cardoso Dos Santos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Recent years have seen efforts to engineer lanthanide complexes for cell-based, TGL biosensing and imaging applications including sensing of pH, metal ions, nucleic acids, enzymatic activities, and PPIs (Aulsebrook et al, 2018;Mathieu et al, 2018;New et al, 2010;Rajendran et al, 2014;Zhang et al, 2018). A number of studies reported proof-of-concept LRET microscopic imaging of molecular interactions between Tb(III)or Eu(III)-labeled and fluorophore-labeled species on cell surfaces including G-protein-coupled receptor (GPCR) ligand binding (Delbianco et al, 2014), GPCR oligomerization (Comps-Agrar et al, 2012;Faklaris et al, 2015), cadherin interactions (Linden et al, 2015), and interactions between complementary morpholino probes in zebrafish embryos (Cho et al, 2018). LRET between Tb(III) complexes and quantum dots on cell surfaces and in zebrafish has been shown to be an effective approach to signal amplification and multiplexing (Afsari et al, 2016;Cardoso Dos Santos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many lanthanide cyclen-based luminescent complexes have been developed for application as optical probes in optical imaging or in cellulo studies. [12][13][14][15] Whatever the targeted medical or biomedical application of a lanthanide complex, the chelate must present a high stability to avoid the toxic effects associated to the dissociation of the complex in vivo. 16,17 Nowadays it is widely recognised that a high kinetic inertness with respect to their dissociation is more important than a high thermodynamic stability of the complex.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Nevertheless, luminescence from lanthanide ions offers unique properties such as al arge (pseudo)S tokes shift, elemental spectral signatures with narrowe mission bands in the visible and near-infrared (NIR) regions, [10] and extremelyl ong excited-state lifetimes. [9] Due to indirect photosensitization through chelating ligands, [11] termedt he "antennae ffect", lanthanide-based labels can have brightnessv alues of the order of 10 4 m À1 cm À1 at their highest, [12] but the association of long lifetimes and line-likee mission bands offers ab road range of opportunities for ultrasensitive multiplexed analysis in bioassays [13] and time-resolved fluorescence microscopy. [14] Somel anthanide-based NPs, [15] and more recently molecular systems, [16] also offer an unrivalled opportunity with upconverting properties, giving an early background-free emissiona th ighere nergy than the excitation light.…”
Section: Introductionmentioning
confidence: 99%